The Influence of the Implementation of International Financial Accounting Standards (IFRS) and Audit Quality - Rahmad Dani; Mardiah Hasanah Nasution; Ayu Andira (International Journal of Economics, Management and Accounting, 2024)
This research was conducted with the aim of analyzing the consequences of implementing IFRS and audit quality on the quality of financial reports in technology sector companies listed on the IDX during the 2019-2022 period. The research method used is a quantitative approach with logistic regression. The research results show that separately, the implementation of IFRS and audit quality have a significant influence on the quality of financial reports in technology sector companies listed on the IDX during the 2019-2022 period. Therefore, from the results of this research, it is recommended that companies focus on implementing standards such as IFRS 15 (Revenue from Contracts with Customers) or IFRS 9 (Financial Instruments) can provide more detailed insight into the practical impact of adopting these standards.